Pengembangan Media Flash Card IPA Terintegrasi Model Two Stay Two Stray Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas 5 SD: Development of Science Flash Card Media Integrated Two Stay Two Stray Model to Improve Critical Thinking Skills of Grade 5 Elementary School - Agil Kurniawati; Mawardi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This research was conducted based on an analysis of the needs and problems found in the SD located in Gugus Mawar, Suruh District. This study aims to develop a media, namely to determine the level of feasibility and practicality of integrated science flash card media with the Two Stay Two Stray (TSTS) model to improve critical thinking skills in 5th grade elementary school. This research and development (Research & Development) chose a research development design using procedures that have been modified by Sukmadinata and using the ASSURE development model. Assessment questionnaire sheets for validator experts and response questionnaire sheets are used as data collection instruments. With that, expert lecturers, students and teachers of grade 5 elementary school were used as the subjects of this study. The results of this study indicate that IPA flash card media is considered feasible and practical with the acquisition of a percentage of material experts 92.7%, media experts 93.8%, and learning design 93.8%. As for the practicality of the media, it got a percentage of 79.2% from student responses and 88% from teacher responses. It can be concluded that the integrated science flash card media using the TSTS model to improve critical thinking skills for grade 5 elementary school is considered feasible and practical to apply to the learning process.